Fabrication of novel oleogel enriched with bioactive compounds and assessment of physical, chemical, and mechanical properties and storage stability - Sivakanthan, S.; Fawzia, S.; Mundree, S.; Madhujith, T.; Karim, A. (Elsevier, 2024)
Amidst evolving dietary challenges, developing oleogels as functional foods enriched with bioactive compounds is gaining dramatic attention. The utilization of fish oil (a source of omega-3 fatty acids) in food is greatly restricted due to its susceptibility to oxidation and the study on the use of fish oil in oleogel is also scanty. β-Carotene and β-sitosterol are lipophilic compounds with several health benefits. Therefore, in this study, oleogels enriched with fish oil, β-carotene, and β-sitosterol were developed and examined for their properties. Oleogels were developed from a basic formula comprising a blend of rice bran oil and sesame oil (4:5, w/w) and a synergistic mixture of beeswax and stearic acid (3:1, w/w) as oleogelators. Fish oil and β-sitosterol were incorporated at 10% (w/w) and 5% (w/w), respectively of the total oil mixture, while β-carotene was included at 0.1, 0.25, 0.5, and 1 % (w/w). The oils and oleogels were evaluated for their properties and storage stability in terms of rheological stability, oxidative stability, and β-carotene content until 4 months of storage. The incor- poration of fish oil did not cause any significant changes in the properties of the oleogels. The incorporation of β-carotene resulted in a more uniform microstructure and increased gel strength, whereas oil binding capacity and thermal and molecular properties of the oleogels were not influenced by β-carotene. Oleogels exhibited higher oxidative stability and less β-carotene loss during storage than the oils. The incorporation of β-carotene enhanced the oxidative stability of the oleogels. The findings of this study suggested that there is a potential for preparing oleogels incorporated with bioactive compounds with good stability.
Keywords: β-carotene; β-sitosterol; Fish oil; Rice bran oil; Sesame oil